Innovations embodied in Japan’s school lunch program - Murayama, Nobuko (2022)
Nobuko Murayama Side Event: How Japan’s know-how can help address food and nutrition challenges in the developing world Tokyo Nutrition for Growth (N4G) Summit 2021 NOV 30, 2021